Soil Additives: Their Effect on Soil Erosion and Vegetation Establishment During the Hydroplanting Process - Frank, John Ray (My University, 1975)
Growth chamber, greenhouse, and field experiments were conducted to evaluate the effect of chemical soil additives on reduction of soil moisture loss, seed germination, establishment of vegetative cover, and soil erosion control when used as a part of the hydroplanting process. Two groups of soil additives were evaluated. Liquid plastic acrylic materials, such as polyvinyl acetates, acrylates, methyl acrylates, and urethane polymers made up one of the groups. The second group consisted of compounds made of natural plant products such as alginates, from deep sea kelps, and gums, which are ground endosperm derivatives. Under controlled growth chamber and greenhouse conditions, acrylic soil additives reduce evaporation or evapotranspiration better than the alginates or other organic plant derivatives. Some acrylics reduce water penetration, while others such as Curasol AE at concentrations of 60 gal per acre, permit adequate water percolation and subsequently support the desired vegetative growth. The results of greenhouse tests using chemical soil additives with wood fiber mulch on 30° topsoil slopes indicate that erosion control on slopes subjected to high amounts of rainfall can be greatly reduced. Landlock II, a urethane polymer which forms a hard crust, did not allow any soil loss; while treatments without wood fiber mulch or additive resulted in approximately 9 tons of soil loss per acre. Wood fiber mulch alone did help control soil loss by nearly 65 percent. In field tests where adequate rainfall was available, soil additives did not improve vegetative cover. Hydroplanting field tests conducted under conditions of limited rainfall and low soil fertility, using wood fiber mulch without chemical soil additives, produced the best grass coverage at 30 days. Evaluations at 150 days indicate that Biobinder used at 120 gal per acre gave the best total vegetative coverage. Bahiagrass seed mixtures and species of bermudagrass were successfully hydroplanted on 30° slopes when applications of Soil Seal at 60 gal per acre and Curasol AE at 60 gal per acre were mixed with wood fiber mulch. No additional soil erosion was observed following treatment. All treatments using soil additives with wood fiber mulch gave good erosion control on 45° sand slopes. Ecology Controls at 200 and 400 lb per acre and the treatments without chemical soil additives provided the best vegetative coverage. The soil additive treatments used on blowing sand greatly reduced wind erosion but the treatment using only wood fiber mulch gave the best vegetative cover while also reducing wind erosion.